Answer:
![\displaystyle a = \frac{1}{3} \text{ and } b = \frac{2}{3}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20a%20%3D%20%5Cfrac%7B1%7D%7B3%7D%20%5Ctext%7B%20and%20%7D%20b%20%3D%20%5Cfrac%7B2%7D%7B3%7D)
Step-by-step explanation:
We can use the definition of inverse functions. Recall that if two functions, <em>f</em> and <em>g</em> are inverses, then:
![\displaystyle f(g(x)) = g(f(x)) = x](https://tex.z-dn.net/?f=%5Cdisplaystyle%20f%28g%28x%29%29%20%3D%20g%28f%28x%29%29%20%3D%20x)
So, we can let <em>j</em> be the inverse function of <em>h</em>.
Function <em>h</em> is given by:
![\displaystyle h(x) = y = 3x-2](https://tex.z-dn.net/?f=%5Cdisplaystyle%20h%28x%29%20%3D%20y%20%3D%203x-2)
Find its inverse. Flip variables:
![x = 3y - 2](https://tex.z-dn.net/?f=x%20%3D%203y%20-%202)
Solve for <em>y. </em>Add:
![\displaystyle x + 2 = 3y](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%20%2B%202%20%3D%203y)
Hence:
![\displaystyle h^{-1}(x) = j(x) = \frac{x+2}{3} = \frac{1}{3} x + \frac{2}{3}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20h%5E%7B-1%7D%28x%29%20%3D%20j%28x%29%20%3D%20%5Cfrac%7Bx%2B2%7D%7B3%7D%20%3D%20%5Cfrac%7B1%7D%7B3%7D%20x%20%2B%20%5Cfrac%7B2%7D%7B3%7D)
Therefore, <em>a</em> = 1/3 and <em>b</em> = 2/3.
We can verify our solution:
![\displaystyle \begin{aligned} h(j(x)) &= h\left( \frac{1}{3} x + \frac{2}{3}\right) \\ \\ &= 3\left(\frac{1}{3}x + \frac{2}{3}\right) -2 \\ \\ &= (x + 2) -2 \\ \\ &= x \end{aligned}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cbegin%7Baligned%7D%20h%28j%28x%29%29%20%26%3D%20h%5Cleft%28%20%5Cfrac%7B1%7D%7B3%7D%20x%20%2B%20%5Cfrac%7B2%7D%7B3%7D%5Cright%29%20%5C%5C%20%5C%5C%20%26%3D%203%5Cleft%28%5Cfrac%7B1%7D%7B3%7Dx%20%2B%20%5Cfrac%7B2%7D%7B3%7D%5Cright%29%20-2%20%5C%5C%20%5C%5C%20%26%3D%20%28x%20%2B%202%29%20-2%20%5C%5C%20%5C%5C%20%26%3D%20x%20%5Cend%7Baligned%7D)
And:
![\displaystyle \begin{aligned} j(h(x)) &= j\left(3x-2\right) \\ \\ &= \frac{1}{3}\left( 3x-2\right)+\frac{2}{3} \\ \\ &=\left( x- \frac{2}{3}\right) + \frac{2}{3} \\ \\ &= x \stackrel{\checkmark}{=} x\end{aligned}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cbegin%7Baligned%7D%20j%28h%28x%29%29%20%26%3D%20j%5Cleft%283x-2%5Cright%29%20%5C%5C%20%5C%5C%20%26%3D%20%5Cfrac%7B1%7D%7B3%7D%5Cleft%28%203x-2%5Cright%29%2B%5Cfrac%7B2%7D%7B3%7D%20%5C%5C%20%5C%5C%20%26%3D%5Cleft%28%20x-%20%5Cfrac%7B2%7D%7B3%7D%5Cright%29%20%2B%20%5Cfrac%7B2%7D%7B3%7D%20%5C%5C%20%5C%5C%20%26%3D%20x%20%20%5Cstackrel%7B%5Ccheckmark%7D%7B%3D%7D%20x%5Cend%7Baligned%7D)
8:15 or 8 to 15 would be the ratio because you compare 8 quarters to 15 coins.
Answer:
![x=\frac{27}{10}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B27%7D%7B10%7D)
Step-by-step explanation:
![\frac{x}{2}-\frac{1}{5}=\frac{x}{3}+\frac{1}{4}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7B2%7D-%5Cfrac%7B1%7D%7B5%7D%3D%5Cfrac%7Bx%7D%7B3%7D%2B%5Cfrac%7B1%7D%7B4%7D)
![\frac{x}{2}-\frac{1}{5}-\frac{x}{3}=\frac{x}{3}+\frac{1}{4}-\frac{x}{3}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7B2%7D-%5Cfrac%7B1%7D%7B5%7D-%5Cfrac%7Bx%7D%7B3%7D%3D%5Cfrac%7Bx%7D%7B3%7D%2B%5Cfrac%7B1%7D%7B4%7D-%5Cfrac%7Bx%7D%7B3%7D)
![-\frac{1}{5}+\frac{x}{6}=\frac{1}{4}](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B5%7D%2B%5Cfrac%7Bx%7D%7B6%7D%3D%5Cfrac%7B1%7D%7B4%7D)
![-\frac{1}{5}+\frac{x}{6}+\frac{1}{5}=\frac{1}{4}+\frac{1}{5}](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B5%7D%2B%5Cfrac%7Bx%7D%7B6%7D%2B%5Cfrac%7B1%7D%7B5%7D%3D%5Cfrac%7B1%7D%7B4%7D%2B%5Cfrac%7B1%7D%7B5%7D)
![\frac{x}{6}=\frac{9}{20}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7B6%7D%3D%5Cfrac%7B9%7D%7B20%7D)
![\frac{6x}{6}=\frac{9\times \:6}{20}](https://tex.z-dn.net/?f=%5Cfrac%7B6x%7D%7B6%7D%3D%5Cfrac%7B9%5Ctimes%20%5C%3A6%7D%7B20%7D)
![x=\frac{27}{10}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B27%7D%7B10%7D)
Answer:
let t = number of three-point shots
let f = number of free throw shots
Step-by-step explanation:
t + f = 9 (he made a total of 9 shots altogether)
3t + 1f = 23 (number of shots multiplied by their point value)
substitution method: t = 9 - f
3(9 - f) + f = 23
27 - 3f + f = 23
-2f = -4
f = 2
find 't': t + 2 = 9
t = 7